The testament of Mary [compact disc, unabridged] - Tóibín, Colm, 1955- (Simon & Schuster, 2013)
Provocative, haunting and indelible, this portrait of Mary presents her as a solitary older woman still seeking to understand the events that become the narrative of the New Testament and the foundation of Christianity. Years after the crucifixion, Mary lives alone and refuses to help the authors of the Gospel. She does not agree that her son is the Son of God; nor that his death was 'worth it'; nor that these mere men that followed him were holy disciples.